2012
DOI: 10.1016/j.jtcvs.2012.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Utility of concomitant tricuspid valve procedures for patients undergoing implantation of a continuous-flow left ventricular device

Abstract: Concomitant TVP appears to reduce postprocedure right ventricular failure for patients with significant TR undergoing cfLVAD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…Therefore, the present results support International Society for Heart and Lung Transplantation guidelines that for moderate or greater TR, the tricuspid valve should be repaired at the time of LVAD implantation. 7,9,11,19 The results also support the studies by Piacentino et al, 10,12,13 which suggest that TVP may help to mitigate RHF for patients with moderate to severe preimplant TR relative to those who do not receive TVP.…”
Section: September 9 2014supporting
confidence: 81%
See 2 more Smart Citations
“…Therefore, the present results support International Society for Heart and Lung Transplantation guidelines that for moderate or greater TR, the tricuspid valve should be repaired at the time of LVAD implantation. 7,9,11,19 The results also support the studies by Piacentino et al, 10,12,13 which suggest that TVP may help to mitigate RHF for patients with moderate to severe preimplant TR relative to those who do not receive TVP.…”
Section: September 9 2014supporting
confidence: 81%
“…10 Preliminary studies suggest that tricuspid valve repair at the time of LVAD implantation may improve early outcomes and reduce RHF. [11][12][13][14] However, John et al 8 demonstrated increased RHF for patients undergoing concurrent tricuspid valve procedures (TVP) versus LVAD alone. It is unclear whether the increased postoperative RHF relates to the severity of preimplant TR or the TVP itself.…”
Section: S4 Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are no studies examining the impact of concomitant TVR on long-term outcomes, such as survival free of transplant, quality of life, and readmission rates. 30 Several single-center studies have examined the short-term impact of this procedure for moderate-to-severe TR 25,[30][31][32] ; however, to our knowledge, there have been no such multicenter studies.…”
Section: Concomitant Tricuspid Valve Repair With Lvad Implantationmentioning
confidence: 99%
“…31,32 The first involved 115 patients with moderate-to-severe TR, 34 of whom underwent concomitant TVR. A related report looked at 200 consecutive patients with continuous-flow LVAD, 61 of whom had moderate-to-severe TR (33 underwent concomitant TVR).…”
Section: Concomitant Tricuspid Valve Repair With Lvad Implantationmentioning
confidence: 99%